Pedagogical conditions of success of professional activity of high school teacher - Shalimova, I. M.; Shalimova, A. S. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses the increasing success of professional work of the university teacher. In our opinion, the success of professional activity (SPA) of high school teacher is provided the functioning of the pedagogical conditions: the constant improvement of professional competence of high school teacher; the creation of the optimal pedagogical interaction at «teacher-student» level and the creation of different types of successful situations. It is proved that the implementation of specified pedagogical conditions will contribute to the development of motivational, cognitive-procedural and reflexive-efficient components of SPA. The article notes that the implementation of specified pedagogical conditions will lead to positive changes in the structure of personality: expansion of the range of interests and changes in the system requirements; actualization motives of professional achievements; increased demand of self-realization and self-development; raising the level of professional competence; improvement of skills; improvement of professionally significant qualities. In accordance with the requirements of the organization and conduct experimental procedure experimental work was designed and installed the main ways of its implementation. During the experimental work were used: the rating score of students in order to identify professional and pedagogical skills, personal qualities that they think as important for the teacher; peer review, i.e. evaluation of teachers by teachers to identify the qualities that are most important to them; self-teacher own teaching activities.